Kajian Sistem Lampu Isyarat Dan Penggunaan Sistem ‘’Actuated’’ - Mohd Jani, Fazilah (Universiti Sains Malaysia, 2006)
Congestion is a problem commonly faced by a fast-developing nation like Malaysia. A major factor that contribute to this problem is the inequilibrium of modal split for travelers on the road. The number of passenger cars which exceed the capacity of infrastructure resulting congestion at intersections especially during peak hours. The installation of traffic signal is one effective method to control traffic to ensure that all vehicles move smoothly trough the intersection. The utilization of Intelligent Traffic Light which system are increasingly becoming common in our country is believed to be reduce the traffic problem especially during the peak hour and will tackle the problems able to associated with major and minor roads. This research will try analyse how far this statement is true and whether the implementation of an actuated system is more efficient compared to the fixed time system. In this thesis also will try to find deeper the meaning of actuated signal system and the efficiency of this signal toward the traffic light intersections.